Quand les engloutis fabulent - Xavier Garnier (Itinéraires)
When violence is unleashed on a territory, a large part of the inhabitants hide away and seek to make themselves invisible by going behind the scenes. This is the case of the narrator of Qui se souvient de la mer, a novel by Mohammed Dib published in 1962. The novel appears as an assessment of the preceding eight-year long nightmare. Beneath a city that strongly resembles Algiers, an underground city unfolds, adjacent to the city at war, taking in all its violence, but seemingly shaped by other narrative rules. This fabulous city not only functions as a refuge, it is also a high intensity black hole where individual traumas coalesce into collective trauma that gives shape to a mysterious urban geography. The words of the invisible inhabitants, explicitly used in Mohammed Dib's novel, turn the story into a fable to spatialize the part of trauma that was born in the colonial era and continues to haunt postcolonial experience. The underground city of Mohammed Dib is a point de vie (“point of life”) on the world, both impregnable and charged with energy.